The Influence Of Organizational Commitment And Work Discipline On Employee Performance At PT. Arnov Energi - Octaviani, Irma Sari (Sean Institute, 2025)
This study examines the influence of organizational commitment and work discipline on employee performance at PT. Arnov Energi. Using a descriptive quantitative method, data were collected through questionnaires, observations, and literature studies from 82 employees. The analysis was conducted using multiple linear regression with SPSS 22. The findings indicate that both organizational commitment and work discipline significantly affect employee performance, both partially and simultaneously. Employees with high commitment and discipline demonstrate better performance, contributing to increased productivity. The coefficient of determination (R²) shows that 86% of employee performance is influenced by organizational commitment and work discipline, while 14% is affected by other factors. To improve performance, PT. Arnov Energi must enhance organizational commitment through engagement strategies and reinforce work discipline through stricter policies. Strengthening these aspects is essential to fostering a competitive and productive workforce.